Neuroeconomic dissociation of semantic dementia and behavioural variant frontotemporal dementia - Chiong, Winston (Brain, 2016)
Many neuropsychiatric disorders are marked by abnormal behaviour and decision-making, but prevailing diagnostic criteria for such behaviours are typically qualitative and often ambiguous. Behavioural variant frontotemporal dementia and semantic variant primary progressive aphasia (also called semantic dementia) are two clinical variants of frontotemporal dementia with overlapping but distinct anatomical substrates known to cause profound changes in decision-making. We investigated whether abnormal decision-making in these syndromes could be more precisely characterized in terms of dissociable abnormalities in patients’ subjective evaluations of valence (positive versus negative outcome) and of time (present versus future outcome). We presented 28 patients with behavioural variant frontotemporal dementia, 14 patients with semantic variant primary progressive aphasia, 25 patients with Alzheimer’s disease (as disease controls), and 61 healthy older control subjects with experimental tasks assaying loss aversion and delay discounting. In general linear models controlling for age, gender, education and Mini-Mental State Examination score, patients with behavioural variant frontotemporal dementia were less averse to losses than control subjects (P < 0.001), while patients with semantic variant primary progressive aphasia discounted delayed rewards more steeply than controls (P = 0.019). There was no relationship between loss aversion and delay discounting across the sample, nor in any of the subgroups. These findings suggest that abnormal behaviours in neurodegenerative disease may result from the disruption of either of two dissociable neural processes for evaluating the outcomes of action. More broadly, these findings suggest a role for computational methods to supplement traditional qualitative characterizations in the differential diagnosis of neuropsychiatric disorders.